2017
DOI: 10.1111/apt.13917
|View full text |Cite
|
Sign up to set email alerts
|

Serum alkylresorcinols as biomarkers of dietary gluten exposure in coeliac disease

Abstract: Serum alkylresorcinol concentrations could be a useful marker for dietary gluten in coeliac disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
2
6
0
Order By: Relevance
“…Although the use of serum alkylresorcinols as a biomarker for a gluten‐free diet remains to be validated in larger studies, several studies have shown its potential 7–9 . The findings in our sample that serum alkylresorcinols were lower after the gluten‐free intervention compared with the gluten‐containing intervention support this, and indicates good compliance to the interventions, which we consider as a strength.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Although the use of serum alkylresorcinols as a biomarker for a gluten‐free diet remains to be validated in larger studies, several studies have shown its potential 7–9 . The findings in our sample that serum alkylresorcinols were lower after the gluten‐free intervention compared with the gluten‐containing intervention support this, and indicates good compliance to the interventions, which we consider as a strength.…”
Section: Discussionsupporting
confidence: 72%
“…Although the use of serum alkylresorcinols as a biomarker for a gluten-free diet remains to be validated in larger studies, several studies have shown its potential. [7][8][9] The findings in our sample that serum alkylresorcinols were lower after the gluten-free intervention compared with the gluten-containing intervention support this, and indicates good compliance to the interventions, which we consider as a strength. Another strength of this study is the adequate blinding of the participants and investigators, and confounding factors were minimised by using the randomised crossover design, 23 and the strict in-and exclusion criteria.…”
Section: Step 4: Secondary Endpoint; Prediction Of Response To the Gl...supporting
confidence: 69%
See 1 more Smart Citation
“…Serum AR concentrations, which can be used as a biomarker for gluten-containing diet in prior investigations, 22,23 were measured using the normal-phase liquid chromatographytandem mass spectrometry (LC-MS/MS), as described elsewhere 24 with some modifications for instrumentation. Briefly, 100 μL of serum was loaded on HybridSPE Plus phospholipid removal 96-well plates (Sigma-Aldrich, St Louis, MO, USA) and recovered with acetone.…”
Section: Measurement Of Alkylresorcinols (Ar)mentioning
confidence: 99%
“…Finally, adherence to diet in intervention studies is always a matter of worry. Even if our measures of serum alkylresorcinols 9 as a biomarker for adhering to a GFD remains to be validated, numerous studies, including a gluten challenge study in healthy volunteers, 10 have shown its potential.…”
mentioning
confidence: 99%